(untitled) (Research, Society and Development, 2025)
Hemophilia is a rare hereditary condition that affects not only physical health but also the psychological and social well-being of those affected. The present study aimed to analyze the contributions of psychological interventions to the quality of life (QoL) and treatment adherence of people with hemophilia, through an integrative literature review. The bibliographic search was carried out between February and April 2025 in the databases SciELO, LILACS, PubMed/MEDLINE, and PsycINFO, using descriptors in Portuguese and English. Following the PRISMA 2020 protocol, 145 records were initially identified, of which 15 articles met the inclusion criteria. The results indicated that psychoeducational interventions, psychological counseling, and empowerment programs had positive impacts in reducing anxiety and depressive symptoms, in addition to promoting greater treatment adherence. It was also observed that the combination of psychological support with pharmacological innovations, such as extended half-life clotting factors (EHL), enhanced functionality indicators and quality of life in adult and adolescent patients. It is concluded that Health Psychology plays an essential role in the comprehensive management of hemophilia and should be systematically incorporated into the multiprofessional practices of blood centers, with emphasis on emotional support, psychoeducation, and strengthening patient autonomy.